Finance in Transition : Unlocking Capital Markets for Vietnam’s Future Development - World Bank (World Bank, Washington, DC, 2019)
The Vietnamese economy has done well in 2019. In the context of increasing global uncertainty,Vietnam will most certainly be among the fastest growing economies in the world, with a GDP growth rate of approximately 6.8 percent. This rate is almost three times faster than the world average (2.6 percent) and 1.2 percentage points higher than the average in East Asia and Pacific, according to the latest estimates from the World Bank’s Global Economic Prospects. This robust growth performance was attained thanks to the contribution of two key factors: export growth and domestic demand from households and firms. The first factor reflects the performance of the exports sector, growing by about 8.4 percent between January and September 2019, which is lower than in the recent past (15.8 percent in the same period in 2018), but three times higher than the global average. However, this expansion can be short-lived as it captures to some extent the diversion of Chinese exports toward Vietnam due to the trade tensions between China and the UnitedStates. As a matter of fact, the value of exports toward non-U.S. markets increased by only 3.8percent in 2019. The second contributing factor reflects the rapid expansion of the middle class, as the number of people living on more than US 15 Dollars per day increases by about 1 million every year. The demand of the burgeoning middle class has been met to a great extent by purchases of foreign products, as the imports of consumption goods have been rising by about 15 percent per year since 2015. The contribution of exports and private demand to GDP growth has allowed the government to maintain its prudent fiscal and monetary policies. On the fiscal front, the authorities have managed to reduce their fiscal deficit (down by 0.1 percent of GDP) due to higher-than-expected revenues and a very low execution of capital investment expenditures; the latter has been persistently low since 2015. As a result, the debt-to-GDP ratio (the Ministry of Finance’s definition) is estimated to have declined from 58.4 to 56.1 percent from 2018 and 2019. The authorities have thus been able to rebuild additional fiscal space by reducing public borrowing by almost 8 percentage points of GDP since 2016, though lower capital spending has also depressed potential growth.